تفسير مفاتيح الغيب لفخر الدين الرازي في ضوء التفسير السيميائي (سورة الشرح أنموذجا): Tafsir Mafatih al-Gaib li Fakhr al-Din al-Razi fi Dau al-Tafsir al-Simyai (Surah al-Syarh Anmuzajan) - Syahran, Muhammad; Mardan, Mardan; Khalid, M Rusydi; Arsyad, Aisyah; Masuwd, Mowafg (Diwan : Jurnal Bahasa dan Sastra Arab, 2024)
يهدف هذا البحث إلى الإجابة عن المشكلة الرئيسة وهي كيف كان التفسير السيميائي في تفسير الرازي لسورة الشرح. وتشكلت المشكلة الرئيسة في ثلاثة، وهي: حقيقة التفسير السيميائي في تفسير الرازي، صورته في سورة الشرح وثمراته في سورة الشرح. والبحث مكتبي بمقاربة علم التفسير التحليلي والمقارن، وسيميائية دي سوسور وبيرس. والبيانات مقروءة الجمع. والتحليلات ستة، وهي: المعنى الوضعي، والمجازي، والمناسبة، واستقلالية اللغة، والتأويل، والمسلمة البنيوية. ونتائجه ثلاثة، وهي: إن حقيقة التفسير السيميائي في تفسير الرازي هي استنباط المعاني الكثيرة من الألفاظ القليلة. وأما صورته في سورة الشرح فهي: قولان، ومسائل، ووجوه. وهي في لفظين: شرح الصدر، ووزرك. وأما ثمراته، فهي: إصلاح معرفة من أنكر شرح الصدر النبوي المادي، وإصلاح معرفة من رجح شرح الصدر النبوي المادي على شرحه الروحي، وإصلاح معرفة من أثبت معصية في حق النبي محمد ﷺ. Abtsract This research aims to address the main question about the way semiotic interpretation is applied in Al-Razi's exegesis of Surah Al-Sharh. The primary problem is divided into three sub-questions; the nature of semiotic interpretation in Al-Razi's exegesis, its manifestation in Surah Al-Sharh, and its outcomes in Surah Al-Sharh. This article is a library-based research employing analytical and comparative exegesis methods, along with the semiotics theories of Saussure and Peirce. Data collection involved extensive reading. The analysis encompasses six aspects: denotative meaning, figurative meaning, relevance, language autonomy, interpretation, and structural postulate. The results are threefold: the essence of semiotic interpretation in Al-Razi's exegesis is the extraction of multiple meanings from a few words. In Surah Al-Sharh, it manifests in two expressions: "expanding the breast" and "the burden." The outcomes are: correcting the understanding of those who deny the physical expansion of the Prophet's breast, correcting the understanding of those who favor the physical expansion over the spiritual, and correcting the understanding of those who attribute sin to the Prophet Muhammad (PBUH).